1984
DOI: 10.1295/polymj.16.731
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Branches in Low-Density Polyethylenes by Fourier Transform Infrared Spectroscopy

Abstract: ABSTRACT:Qualitative and quantitative analysis of short chain branches was carried out on a series oflow-density polyethylenes by Fourier transform infrared spectroscopy. The peak position of the methyl symmetrical deformation bands around 1378 em -1 was found to vary with the type of branches and used for identification of the branch type in low-density polyethylenes. The reciprocals of extinction coefficients of the methyl deformation bands were determined for various branch types on the basis of 13 C NMR da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…They were determined by NMR studies of some commercial LDPEs. 4 According to these values, in LDPE (grade LF0200), butyl short branches per 100 carbon atoms must be This is in good agreement with the method introduced here.…”
Section: Determination Of Butyl Branches In the Resinsupporting
confidence: 80%
See 1 more Smart Citation
“…They were determined by NMR studies of some commercial LDPEs. 4 According to these values, in LDPE (grade LF0200), butyl short branches per 100 carbon atoms must be This is in good agreement with the method introduced here.…”
Section: Determination Of Butyl Branches In the Resinsupporting
confidence: 80%
“…In LDPE, however, SCBD is more complex because short-chain branches (SCB) are produced by intramolecular chain transfer or backbiting of the growing radical, 3 whereas in LLDPE, SCB are introduced into the backbone by the copolymerization of ethylene with a-olefins; this makes it possible to introduce certain select types of SCB into LLDPE. 4 A variety of techniques have been used to measure SCB and their distribution in LDPE, such as infrared (IR) spectroscopy, 5-8 1 H-and 13 C-NMR spectroscopy, 9,10 pyrolysis hydrogenation/gas chromatography, 11,12 and g-radiolysis. 13 Among these methods, only spectroscopic methods have provide direct measurements of SCB, and IR spectroscopy has attracted more attention because of its simplicity, speed, and low equipment cost.…”
Section: Introductionmentioning
confidence: 99%
“…In the table, information on short-chain branches is also provided. The number of short-chain branched was measured by Fourier-transfer Infra-red spectroscopy using the method proposed by Usami and Takayama [50]. Moreover, the apparent flow activation energy is evaluated by the rheological shift factors at various temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…Since it is generally accepted that a high viscous polymer melt slips on the wall, the slippage can be the origin of surface instability [35,43,44]. Gross melt fracture is attributed to the flow instability at a die entrance, and associated with long time relaxation mechanism [38,[45][46][47][48][49][50][51]. Yamaguchi et al found that gross melt fracture of LDPE can be avoided by applying intense shear history, which weakens the relaxation mechanism associated with long-chain branches, by shear modification [51].…”
Section: Introductionmentioning
confidence: 99%
“…Films of the extracted polymers were cast at 130°C by applying a 12 bar pressure for 72 s and then analyzed by a Perkin-Elmer 1600 FT-IR spectrophotometer. The number of vinyl and vinylidene end-groups per 1,000 carbon atoms was evaluated according to the procedure reported by Usami and Takayama (29).…”
mentioning
confidence: 99%